KONSEP KEBAHAGIAAN RUMAH TANGGA PERSPEKTIF KARL MARX DAN AL-GHAZALI (SUATU PERBANDINGAN) - Ali Mutakin; Miftah Farid; Khaeruddin Khaeruddin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
Forms of domestic happiness have the value of materialism and idealism. Materialism can be interpreted as attached to products, wealth, and worldly objects. Meanwhile, the value of idealism emphasizes the importance of the superiority of the mind, soul or spirit rather than things that are material or material. The data of this study were collected through a literature study that outlined data based on the formulation of the problem How is happiness according to the concept of mathematicalism of Karl Marx and the sufistic al-Ghazali and its application of the Household? The result of the research is that Happiness according to Karl Marx is essentially created because of the material, namely in the form of property and economic establishment and social conditions, while according to al-Ghazali, namely by knowing oneself, then you will know Allah Almighty by having knowledge and charity, being sure, purifying the soul and, perfecting the soul. The implementation of Karl Max's concept of materialism towards household happiness, namely economic stability, is what can bring a happy household in other words, material is the source of happiness in the form of property. Meanwhile, according to al-Ghazali, happiness will be created in the household, when the household becomes a field of worship to be close to Allah.